PENGARUH STRUKTUR MODAL, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN SUBSEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BEI PERIODE 2020-2022) - Palijama, Febiyanti; Usmany, Alfrin Ernest Marthen (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2025)
The company's financial performance is one of the factors that can be used to see the company's condition in a certain period in generating profits. The ratio used to measure financial performance is Return On Asset (ROA). This study aims to empirically examine the effect of capital structure, liquidity and company size on the financial performance of Telecommunication subsector companies listed on the IDX in 2020-2022. This research uses quantitative methods using secondary data. The population used is all telecommunication subsector companies listed on the IDX in 2020-2022 totaling 21 companies with 63 samples. The results of this study indicate that capital structure has a negative effect on financial performance, liquidity has no effect on financial performance, and company size has a positive effect on financial performance.